2021
DOI: 10.1186/s40337-021-00444-2
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, stress, and binge eating tendencies in adolescence: a prospective approach

Abstract: Background Recent years have witnessed an increasing prevalence of binge eating tendencies in adolescence—warranting a clearer understanding of their underlying predisposing and precipitating factors. The current study investigated whether the interaction between high levels of anxiety and stress predicted increased levels of binge eating tendencies in a prospective cohort of adolescents (N = 324). Methods Measurements were taken over three waves (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 97 publications
(130 reference statements)
1
5
0
1
Order By: Relevance
“…Moreover, physical anxiety was the most central node, in accordance with prior longitudinal research with adolescents (Puccio et al, 2017), and also with a network study reporting strong interconnectedness between anxiety and ED symptoms in patients with EDs (Forrest et al, 2019). Anxiety symptoms were also associated with binge behavior, and minimally associated with compensatory behavior, which fits with literature (Lim et al, 2021; Martín et al, 2019). Thus, our findings highlight the role of physical anxiety and cognitive depressive symptoms as factors involved in the association between ED symptoms and SI, as observed by Gómez del Barrio et al (2022).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, physical anxiety was the most central node, in accordance with prior longitudinal research with adolescents (Puccio et al, 2017), and also with a network study reporting strong interconnectedness between anxiety and ED symptoms in patients with EDs (Forrest et al, 2019). Anxiety symptoms were also associated with binge behavior, and minimally associated with compensatory behavior, which fits with literature (Lim et al, 2021; Martín et al, 2019). Thus, our findings highlight the role of physical anxiety and cognitive depressive symptoms as factors involved in the association between ED symptoms and SI, as observed by Gómez del Barrio et al (2022).…”
Section: Discussionsupporting
confidence: 90%
“…Findings from Germany [ 6 , 7 ] and many other countries [ 8 ] revealed high levels of psychological distress as well as symptoms of anxiety and depression in large parts of the general population. It is well accepted that food intake may serve as a coping strategy in dealing with uncomfortable feelings and difficult aspects of life in affluent societies [ 9 , 10 ]. Besides longtime lockdown, perceived nutritional insecurity and confinement force people to develop new routines of daily activities such as meal planning.…”
Section: Introductionmentioning
confidence: 99%
“…However, when mothers reported on emotional and behavioral problems of their children, only associations between emotional problems and LOC eating and of behavioral problems with overeating were found. Prospective studies in adolescents indeed suggest that negative affect, anxiety, stress and attentional impulsivity may predict binge eating symptoms [ 19 , 29 , 62 , 63 ]. Moreover, the direction of effects between binge eating symptoms and depression may differ by type of symptom: a bi-directional association of depressive symptoms with overeating and binge eating was observed in previous research over a one-year period, while a unidirectional association was observed from depressive symptoms towards LOC eating [ 64 ].…”
Section: Discussionmentioning
confidence: 99%